The endophytic microbiome response patterns of Juglans regia to two pathogenic fungi - Wang, Ziye; Xu, Lu; Lu, Xiaoyue; Wang, Ruidong; Han, Jie; Yan, Aihua (Frontiers in Microbiology, 2024)
Endophytic microbial community reassembles to participate in plant immune balance when the host plants are stressed by pathogens. However, it remains unclear whether this assembly is pathogen-specific and how regulatory pathways are coordinated in multi-pathogens. In order to investigate the effects of infection with Colletotrichum gloeosporioides (Cg treatment) and Fusarium proliferatum (Fp treatment) on walnut leaf endophytic microbiome in their assembly, co-occurrence pattern, and on comprehensive chemical function of the leaf's internal environment, an interaction system of the walnut-pathogenic fungi was constructed using seed embryo tissue culture technology. The study showed differences in the assembly of endophytic microbial communities in walnut trees across three groups (control group, Ck; Cg; Fp) after Cg and Fp treatments. Despite changes in relative abundances, the dominant communities in phyla and genera remained comparable during the infection of the two pathogens. Endophyte fungi were more sensitive to pathogen's challenge than endophyte bacteria. Both promoted the enrichment of beneficial bacteria such as Bacillus and Pseudomonas, changed the modularity of the community, and reduced the stability and complexity of the endophyte community. Pathogenic fungi infection mainly affected the metabolism of porphyrin and chlorophyll, purine metabolism, phenylpropane metabolism, and amino acid metabolism. However, there was no significant difference in the secondary metabolites for the different susceptible plants.By screening endogenous antagonistic bacteria, we further verified that Pseudomonas psychrotolerans and Bacillus subtilis had inhibitory effects on the two pathogenic fungi and participated in the interaction between the leaves and pathogenic fungi. The antibacterial substances may be 1-methylnaphthalene, 1,3 butadiene, 2,3-butanediol, and tolualdehyde.